Pengaruh Post-Run Coffee Terhadap Keberlanjutan UMKM Coffee Shop Melalui Perilaku Konsumen Generasi Z - Evy Nurachma; Arkanudin Rizki Permono; Arus Reka Prasetia; Sumarsid (Paraduta : Jurnal Ekonomi dan Ilmu-Ilmu Sosial, 2026)
The rapid growth of coffee shops in major cities has occurred alongside the rise of running culture (run clubs) among urban communities, particularly Generation Z. The phenomenon of “post-run coffee” the habit of stopping by a coffee shop after a running session has become a new touch point between sports communities and small and medium coffee shop enterprises (UMKM). This study aims to analyze the influence of post-run coffee on the sustainability of coffee shop UMKM through the consumer behavior of Generation Z, using the Stimulus-Organism-Response (SOR) framework, in which post-run coffee is positioned as the stimulus, Generation Z's behavior and purchase decisions as the organism-response, and UMKM sustainability as the outcome. The study employed a descriptive qualitative approach through informal, unstructured interviews with 33 members of running communities across several major cities. The results reveal two behavioral patterns: a tendency to visit the same familiar coffee shop (fixed spot) and a tendency to switch between coffee shops depending on the running route (varied spot), as well as the role of community bonus or membership programs in encouraging repeat visits. A scatter plot of the 33 informants indicates that runners who are community members or regular customers show a stronger relationship between running frequency and post-run visit frequency compared to general runners. These findings suggest that partnerships between coffee shop UMKM and running communities, supported by relevant loyalty programs, can serve as a viable business sustainability strategy amid intense competition in the coffee shop industry.